Synthese und Isolierung von Nonafulven - M. Neuenschwander; A. Frey (CHIMIA)
Nonafulvene is prepared by reaction of lithium cyclononatetraenide with acetoxybromomethane at −40 to −25°, followed by elimination of acetic acid with KOC(CH3)3. The title compound, being termally extremely instable, is purified and isolated at low temperatures. The spectroscopic evidence of nonafulvene is presented.